1992
DOI: 10.1210/mend.6.4.1584221
|View full text |Cite
|
Sign up to set email alerts
|

The estrogenic and antiestrogenic properties of tamoxifen in GH4C1 pituitary tumor cells are gene specific.

Abstract: We have examined the effects of the antiestrogen tamoxifen (TAM) and the estrogen 17 beta-estradiol (E2) on several estrogen-regulated responses in GH4C1 pituitary tumor cells. After 5 days of treatment with either TAM (1.0 microM) or E2 (1.0 nM), the level of PRL mRNA was markedly increased when measured by the cytosolic dot blot procedure. In contrast, only E2 was able to increase the levels of beta-actin mRNA and cytosolic protein, suggesting that this estrogen may stimulate cell proliferation over the cour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Also in line with the possibility that anti-oestrogens interfere with growth factor action is the idea that although the oestrogen-liganded ERs might have no effect, the ERs liganded by anti-oestrogens could interfere with the ability of peptide-induced nuclear factors to activate tran¬ scription of growth-promoting genes. Although at present we cannot directly address this question for growth, for two oestrogen-regulated proteins, namely prolactin and the progesterone receptor (PR) (Shull et al 1992), the above would appear not to be the case. Therefore both prolactin secretion measured under conditions that reflect synthesis and PRs measured by the binding of the synthetic ligand R5020 are increased by OE2.…”
Section: Discussionmentioning
confidence: 95%
“…Also in line with the possibility that anti-oestrogens interfere with growth factor action is the idea that although the oestrogen-liganded ERs might have no effect, the ERs liganded by anti-oestrogens could interfere with the ability of peptide-induced nuclear factors to activate tran¬ scription of growth-promoting genes. Although at present we cannot directly address this question for growth, for two oestrogen-regulated proteins, namely prolactin and the progesterone receptor (PR) (Shull et al 1992), the above would appear not to be the case. Therefore both prolactin secretion measured under conditions that reflect synthesis and PRs measured by the binding of the synthetic ligand R5020 are increased by OE2.…”
Section: Discussionmentioning
confidence: 95%
“…The mechanisms by which ligands for nuclear receptors exhibit both agonism and antagonism are not clear. Molecules exhibiting such a mixture of activities have been identified that act to antagonize the actions of ligands for many members of the nuclear receptor family, including androgens, estrogens, and progestins (12,(24)(25)(26)(27)(28). Detailed studies of the activities of such compounds have suggested models in which the receptor assumes distinct conformations that permit the liganded receptor to interact with the transcription apparatus in a productive or nonproductive fashion (29,30).…”
Section: Discussionmentioning
confidence: 99%